1966
DOI: 10.1021/ba-1966-0055.ch031
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Structure of Coals of Different Rank

Abstract: The distribution of hydrogen types in the soluble fractions from the depolymerization of a series of coals has been determined by NMR analysis. The aromatic hydrogen content varies from 20 to 32% of the total hydrogen, and no simple relationship exists with coal rank. β-Paraffinic plus naphthenic hydrogens, the major type, exceed the α-hydrogens and comprise 38-66% of the nonaromatic hydro gens. The most striking variation in the structure of the six coals is the number of methylene bridges. The degree of depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…The structure of coal is complex [2][3][4][5] ; the simplified composition contains angstrom or nanometre-sized crystalline carbon domains with defects that are linked by aliphatic amorphous carbon 6 . Although research on the chemistry of coal has been reported [7][8][9] , the angstrom-and nanoscale crystalline domains of coal are so small and difficult to access so as to impede their further use in electrical, mechanical and optical applications.…”
mentioning
confidence: 99%
“…The structure of coal is complex [2][3][4][5] ; the simplified composition contains angstrom or nanometre-sized crystalline carbon domains with defects that are linked by aliphatic amorphous carbon 6 . Although research on the chemistry of coal has been reported [7][8][9] , the angstrom-and nanoscale crystalline domains of coal are so small and difficult to access so as to impede their further use in electrical, mechanical and optical applications.…”
mentioning
confidence: 99%
“…The sp 3 ratio is measured to be the percentage of sp 3 area. The increase of sp 3 content should be partly ascribed to the generation of nanodiamonds. Considering the amorphous carbon in assynthesized samples possessing the sp 3 component, the yield of the synthesized nanodiamonds was estimated to be 5-10% in our case.…”
Section: Resultsmentioning
confidence: 99%
“…1 As a molecular solid, coal has a complex structure. [2][3][4][5] The crystalline carbon within the coal structure consists of abundant irregular, polymerized aromatic hydrocarbon units, such as angstrom-or nanometer-sized crystalline carbon domains that are joined by weak cross-links. 6,7 Compared with crystalline carbon allotropes, so-called lattice solids, such as graphite and diamond that have found applications in areas such as microelectronics, optoelectronics and biomedicine, 8,9 coal is mainly used as a combustible energy resource due to its structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 36,37,38 ] Out of these conversion processes, the hydrothermal carbonization process is gaining impact because of its potential to convert wet biomass into valuable products. [ 39 ] Among some of the few existing graphene production methods, biomass‐derived graphene is a topic of growing interest for many concrete reasons. Firstly, biomass substances are highly rich in carbon and the biomass‐derived graphene structures are naturally porous that plays a great deal in easy penetration of the electrolyte substances thereby reducing the distance of ion diffusion.…”
Section: Raw Materials For the Synthesis Of Graphenementioning
confidence: 99%